Record review of post-haemodialysis blood results to assess adherence to guidelines for end stage renal disease - van der Nest, Yolinda Louise (Department of Clinical Laboratory Sciences, 2021)
Background: End Stage Renal Disease is an irreversible decline in kidney function and fatal in the absence of renal replacement therapy. Resource constraints in the South African public healthcare sector limits patients' access to renal replacement therapy: here 14.8% are on haemodialysis compared to 85.2% in private dialysis units. Quality indicators in internationally accepted guidelines address complications of End Stage Renal Disease for patients on haemodialysis to reduce mortality and morbidity. Monitoring clinical outcomes for patients on haemodialysis is essential for good quality of life. Aim: To design and validate a record review template for monitoring and describing target and actual outcomes for each clinical indicator to assess adherence to established guidelines. Methods Design: Retrospective chart review. Participants: Patient records were accessed from an electronic database in 8 private units between 01 January and 31 December 2018. Data instruments: Data were captured and analysed in SPSS. DAG Stat was used for the Kappa statistic for interrater reliability (test-retest). A P-value of <0.05 was taken as significant. Results: Of the dialysis population (N=412) for the study period n=243 (58.98%) records were excluded. The median age of the convenience sample (169/412, 41.01%) was 60 years (IQR: 21-86), comprising 100/169 (59.17%) males and 69/169 (40.8%) classified as Coloured. Most patients (55/169, 32.54%) had Diabetic Nephropathy. Suboptimal dialysis adequacy (Kt/V levels) was present in 86/133 (64.6%) of the patients, similarly 102/166 (62.5%) for serum phosphate. Arterio-venous fistula or graft is recommended for vascular access for HD and 112/169 (66.27%) patients had either. While all patients should receive erythropoiesis stimulating agents and iron therapy, 110/169 (65.08%) and 104/169 (61.53%) respectively did. For the required phosphate binders and Vitamin D supplements there were recordings for 57/169 (33.72%) and 54/169 (32.72%) patients respectively. Conclusion: Adherence to clinical guidelines for 3/5 quality indicators was considered unsatisfactory which has implications for patients' quality of life.